Prognostically Important Molecular Markers in Cytogenetically Normal Acute Myeloid Leukemia - Lin, Tara L. (Am J Med Sci, 2011)
Cytogenetically normal acute myeloid leukemia (CN-AML) is a heterogeneous disease with variable clinical outcomes. Emerging data has identified molecular markers that provide additional prognostic information to better classify these patients into those with a more favorable prognosis and those with an unfavorable prognosis who may require more aggressive or investigational therapies. Markers such as mutations in nucleophosmin 1 gene and CCAAT/enhancer binding protein alpha gene have been associated with a more favorable prognosis in CN-AML. In contrast, FMS-related tyrosine kinase 3 mutations, partial tandem duplication of mixed-lineage leukemia gene and overexpression of brain and acute leukemia, cytoplasmic gene are associated with inferior clinical outcomes. In this article, the authors discuss the classical clinical features of AML and the importance of cytogenetics that predict prognosis in AML. They review the best-described molecular markers in CN-AML and their significance to clinical decision making in CN-AML.